Transmission of macro shocks to loan losses in a deep crisis: the case of Finland - Esa Jokivuolle; Matti Virén; Oskari Vähämaa (Bank of Finland, 2009)
Building on the work of Sorge and Virolainen (2006), we revisit the data on aggregate Finnish bank loan losses from the corporate sector, which covers the Big Five crisis in Finland in the early 1990s. Several extensions to the empirical model are considered. These extensions are then used in the simulations of the aggregate loan loss distribution. The simulation results provide some guidance as to what might be the most important dimensions in which to improve the basic model. We found that making the average LGD depend on the business cycle seems to be the most important improvement. We also compare the empirical fit of the annual expected losses over a long period. In scenario-based analyses we find that a prolonged deep recession (as well as simultaneity of various macro shocks) has a convex effect on cumulative loan losses. This emphasizes the importance of an early policy response to a looming crisis. Finally, a comparison of the loan loss distribution on the eve of the 1990s crisis with the most recent distribution demonstrates the greatly elevated risk level prior to the 1990s crisis.
URN:NBN:fi:bof-20140807643
Keywords: 330